Dairy Agribusiness to Improve Farmers’ Welfare in Kabupaten Banyumas - Novie Andri Setianto; Sri Mastuti; Oentoeng Edy Djatmiko; Lucie Setiana; Yusmi Nur Wakhidati; Nunung Noor Hidayat (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2022)
This study aimed to identify factors affecting the dairy agribusiness, to develop mapping for dairy agribusiness development and to determine its strategy improvement. Action research was undertaken followed by descriptive quantitative statistics analysis to present the current condition of the business. Potency and constrains of dairy farming were identified using SWOT analysis. LQ (Location Quotient) analysis followed by series of focus group discussions was conducted to develop the grand design of dairy agribusiness. Research showed that trend of the dairy cow population in Banyumas is relatively stagnant despite an increasing trend on the previous year. LQ analysis showed that sub districts suitable as the basis for dairy development are Kecamatan Baturraden, Pekuncen, Karanglewas, Kedungbanteng and Cilongok. SWOT analysis reported that dairy farming in Banyumas is at quadrant I which indicates an S-O (Strength – Opportunity) strategy focusing on utilizing the strength to maximize the opportunity existed to improve the productivity of dairy cattle.